Helmintos de la República de Costa Rica VIII. Nematoda 2. Algunos nemátodes de Bufo marinus marinus (L) y algunas consideraciones sobre los géneros Oxysomatium y Aplectana - Brenes, Rodrigo Ramón; Bravo Hollis, Margarita (Revista de Biología Tropical, 1959)
The authors discuss the status of the genera Oxysomatium Railliet & Henry, 1913, and Aplectana Railliet & Henry, 1916; in agreement with SKRJABIN'S reduction of the latter to synonymy of the former, new combinations are published and annotated, clarifying the position of several species of Aplectana described in recent years. Redescriptions are presented of four nematode parasites of Bufo marinus marinus (L.) not previously recorded from Costa Rica. Oxysomatium itzocanensis (Bravo, 1947) Skrjabin, 1951, whose range is thus established as from the State of Puebla, México, to Costa Rica; Rhabdias sphaerocephala Goodney, 1924; Oswaldocruzia subanricularis (Rudolphi, 1819) Travassos, 1917, known also from Brazil and Mexico; and Ochoterenella digiticauda Caballero, 1944.